A comparative analysis of risk factors and stroke risk for Asian and non‐Asian men: The Asia Pacific Cohort Studies Collaboration. Issue 8 (22nd October 2013) - Hyun, Karice K.; Huxley, Rachel R.; Arima, Hisatomi; Woo, Jean; Lam, Tai Hing; Ueshima, Hirotsugu; Fang, Xianghua; Peters, Sanne A. E.; Jee, Sun Ha; Giles, Graham G.; Barzi, Federica; Woodward, Mark
<x xml:space="preserve">Abstract</x> Background The risk of stroke is high in men among both Asian and non‐Asian populations, despite differences in risk factor profiles; whether risk factors act similarly in these populations is unknown. Aim To study the associations between five major risk factors and stroke risk, comparing Asian with non‐Asian men. Methods We obtained data from the Asia Pacific Cohort Studies Collaboration, a pooled analysis of individual participant data from 44 studies involving 386 411 men with 9·4 years follow‐up. Using cohorts from Asia and Australia/New Zealand Cox models were fitted to estimate risk factor associations for ischemic and haemorrhagic stroke. Results We identified significant, positive associations between all five risk factors and risk of ischemic stroke. The associations between body mass index, smoking, and diabetes with ischemic stroke were comparable for men from Asia and Australia/New Zealand. The association between systolic blood pressure and ischemic stroke was stronger for Asian than Australia/New Zealand cohorts, whereas the reverse was true for total cholesterol. For haemorrhagic stroke, only systolic blood pressure and smoking were associated with increased risk, although the relationship with systolic blood pressure was significantly stronger for men from Asia than Australia/New Zealand (Pinteraction = 0·03), whereas the reverse was true for smoking (Pinteraction = 0·001). There was an inverse trend of total cholesterol with haemorrhagic stroke, significant only for Asian men. Conclusions Men from the Asia‐Pacific region share common risk factors for stroke. Strategies aimed at lowering population levels of systolic blood pressure, total cholesterol, body mass index, smoking, and diabetes are likely to be beneficial in reducing stroke risk, particularly for ischemic stroke, across the region.